2012
DOI: 10.1007/s00381-012-1747-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AMPA receptor subunits in hippocampus after status convulsion

Abstract: Immature brain was more resistant to seizure-induced neural damage. The time course of reduction and recovery differed for each subunit and was dependent on developmental stage. The increased expression of GluR2 could confer early but transient protection in the immature brain after SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…In addition, pilocarpine has been shown to induce oxidative brain damage when administered systemically, but not intracerebroventricularly, even though a different dosage and localization of lateral ventricle with respect to the bregma was used compared with the present study [16]; therefore, we speculate that the wide diffuse distribution of the drug into the brain through the lateral ventricle may account for the distinct results observed. In addition to the fact that intracerebroventricular pilocarpine administration provides a good distribution of drug into the brain including the hippocampus, it has been shown that this region showed neurodegeneration, neuronal loss (by necrosis or apoptosis), and gliosis after the administration of pilocarpine in rats [20][21][22][23]; however, additional experiments are necessary to determine the spread of damage in the hippocampus by intracerebroventricular pilocarpine administration. In summary, we believe that this model of TLE, unlike the systemic model, is a good alternative for researching the mechanisms underlying the generation and maintenance of seizures, considering that the animals were injected with a single dose of .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pilocarpine has been shown to induce oxidative brain damage when administered systemically, but not intracerebroventricularly, even though a different dosage and localization of lateral ventricle with respect to the bregma was used compared with the present study [16]; therefore, we speculate that the wide diffuse distribution of the drug into the brain through the lateral ventricle may account for the distinct results observed. In addition to the fact that intracerebroventricular pilocarpine administration provides a good distribution of drug into the brain including the hippocampus, it has been shown that this region showed neurodegeneration, neuronal loss (by necrosis or apoptosis), and gliosis after the administration of pilocarpine in rats [20][21][22][23]; however, additional experiments are necessary to determine the spread of damage in the hippocampus by intracerebroventricular pilocarpine administration. In summary, we believe that this model of TLE, unlike the systemic model, is a good alternative for researching the mechanisms underlying the generation and maintenance of seizures, considering that the animals were injected with a single dose of .…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that most of these models also represent animal models of epileptogenesis; considering the aim of this review, we only include discussion of relevant changes within the first 24 hours after the initiation of SE, which might be considered relevant to this phenomenon, although some processes may also be linked to epileptogenesis . Some of these studies have underscored how changes in the expression of AMPARs could be subunit and brain‐region specific . However, these studies focused particularly on temporal lobe regions and above all on the hippocampus and piriform cortex, describing seemingly contradictory results with augmented, reduced, or unchanged AMPARs subunit expression.…”
Section: Ampa Receptors In Status Epilepticusmentioning
confidence: 99%
“…30 Moreover, GluA2-lacking AMPA receptors promote excitotoxicity and neurodegeneration by means of Ca 2+ entry in neurons that normally express Ca 2+ -impermeable channels contributing to, or causing, delayed cell death in response to endogenous glutamate. 21,31,32 Relevant plastic changes in the expression and functioning of AMPARs, and particularly in their subunit composition, have been demonstrated already during early stages of SE in several animal models including the lithium-pilocarpine, 33,34 pilocarpine-, 35 kainate-induced SE 36,37 (Table 1).…”
Section: Ampa Receptors In Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation
“…This is determined by the permeability of the receptor to Ca 2+ ions, and is dependent on the expression of the GluA2 subunit which limits Ca 2+ permeability [248]. Epilepsy is common in ASD and FXS, and AMPARs are implicated in its pathophysiology and treatments [249, 250]. This is a broad topic that is a subject of a review on its own.…”
Section: Ampar Alterations In Animal Models Of Asd and Fxs And Inmentioning
confidence: 99%